1996
DOI: 10.1177/089033449601200317
|View full text |Cite
|
Sign up to set email alerts
|

Social Status, Mother-infant Time Together, and Breastfeeding Duration

Abstract: Chart review and direct observation were used to study the relationship between social status, mother-infant time together, and breastfeeding duration among 138 mothers who were breastfeeding at hospital discharge. Overall breastfeeding rate was 73 percent for patients with private insurance and 37 percent for patients without private insurance. Breastfeeding duration to six months was not related to social status. Mother-infant time together from birth through 48 hours was 3 hours greater for private insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Among foragers, "divorce or paternal death leads to high rates of child mortality among the Ache, the Hiwi, and the !Kung, but not the Hadza" (Kaplan et al 2000:173). Similar to findings for foragers, in the world's large-scale "industrial" populations, public health studies consistently find that single mothers tend to wean their children earlier than do women living with a mate (Bar-Yam and Darby 1997; Kiehl et al 1996;Pande et al 1997;Vega Lopez and Gonzalez Perez 1993). This association is probably related to the trade-off between breastfeeding and women's work (Arlotti et al 1998;Fein and Roe 1998;Visness and Kennedy 1997) that may be particularly pressing among single mothers.…”
Section: Why Do Humans Form Pair-bonds?mentioning
confidence: 75%
“…Among foragers, "divorce or paternal death leads to high rates of child mortality among the Ache, the Hiwi, and the !Kung, but not the Hadza" (Kaplan et al 2000:173). Similar to findings for foragers, in the world's large-scale "industrial" populations, public health studies consistently find that single mothers tend to wean their children earlier than do women living with a mate (Bar-Yam and Darby 1997; Kiehl et al 1996;Pande et al 1997;Vega Lopez and Gonzalez Perez 1993). This association is probably related to the trade-off between breastfeeding and women's work (Arlotti et al 1998;Fein and Roe 1998;Visness and Kennedy 1997) that may be particularly pressing among single mothers.…”
Section: Why Do Humans Form Pair-bonds?mentioning
confidence: 75%
“…In a later study, researchers surveyed 100 privately insured women who were breastfeeding at hospital discharge and then again at 6 months postpartum (Kiehl, Anderson, Wilson, & Fosson, 1996). Women who received EA had lower rates of breastfeeding at 6 months (30% vs. 50% continuation).…”
Section: Use Of Epidural Anesthesia During Labor and Birthmentioning
confidence: 99%
“…The dose of bupivacaine in the epidural anesthesia was a predictor of diminished mother-baby time and of diminished performance of exposed infants on mean orientation and motor cluster scores on the Neonatal Behavioral Assessment Scale. Another study, however, found that mother-baby time together in the first 48 hours after birth was not associated with the proportion still breast-feeding at 6 months, 20 but it did not examine early breast-feeding effects of mother-baby time together. Our study did not include assessments of mother-baby time while in the hospital as a possible explanation for negative breast-feeding effects of epidurals.…”
Section: Discussionmentioning
confidence: 96%
“…Limitations of our study include lack of information regarding length and difficulty of labor, fluid balance, mother-baby time together, and medication type and dosage. We also did not include long-term follow-up (which showed a negative association of epidural anesthesia and breastfeeding rate at 6 months in one study, 20 and negative effects of maternal work in another 19 ). Further studies are needed to clarify the relation between epidural anesthesia and breast-feeding.…”
Section: Discussionmentioning
confidence: 99%